Social segregation and gated communities in Santiago de Chile and Buenos Aires: A comparison - Borsdorf, Axel (2016)
The two Cono Sur capitals share similarities (effects of globalization, socio-spatial segregation, fragmentation, rise of gated cities, social housing in remote locations lacking public transport), however a variety of differences can be observed. Whereas in Santiago gated communities are widespread in the urban fabric, in Buenos Aires these communities are concentrated only in the north and northwestern parts of the city. In Chile parcelas de agrado with more than 5000 m2 fulfill the demand of upper class citizens for more space for luxury villas. Ethnic segregation is seen as a problem in Santiago, where Peruvian immigrants occupy some sectors of the city centre, whereas in Buenos Aires most immigrants are coming from non-metropolitan regions of Argentina. Last not least gentrification in quite strong in Santiago's central communes, whereas the Argentines in a quite unusual way interpret the development of gated communities as a process of social upgrading.